The Effect of Education And Poverty on Human Quality of Life in the Regencies/Cities in Papua Province 2019 to 2023 - LESMANA, Inka Putri; DEWI, Dita Dismalasari (Journal of Tourism Economics and Policy, 2025)
Papua is one of the provinces with the lowest Human Development Index (HDI) in Indonesia. This study aims to examine the effect of education and poverty on the quality of human life in the regencies/cities of Papua Province from 2019 to 2023. This study uses secondary data with a panel data regression analysis method and a Random Effect Model (REM). Econometric tests examine classical assumptions to ensure model validity and use T-tests, F-tests, and the Coefficient of Determination tests. The results show that education has a positive and significant effect on human quality of life, while poverty has a significant negative effect on human quality of life. This study shows that the variables of education and poverty together have a significant effect on human quality of life.